The King and I - Landon, Margaret Dorothea (Mortenson) 1903-; Lehman, Ernest 1915-; Rodgers, Richard 1902-; Hammerstein, Oscar 1895-1960; Kerr, Deborah 1921-; Brynner, Yul; Moreno, Rita; Lang, Walter (Twentieth Century-Fox., 1956)
A musical comedy-drama about an English widow who, with her ten-year-old son, goes to Siam in 1862 to educate the King's wives and children in the ways of western culture and subtly influences the King.